Multi-detector computed tomography evaluation of suspected acute blunt cervical spine trauma in adult patients at King Chulalongkorn Memorial Hospital - Surawech, Chuthaporn; Petcharunpaisan, Sasitorn (Chulalongkorn Medical Journal, 2023)
Background : According to the American College of Radiology (ACR) appropriateness criteria for imaging of suspected spine trauma, multi-detector computed tomography (MDCT) is the recommended screening imaging procedure in adult patients with high-risk criteria by national emergency x-radiography utilization study (NEXUS) criteria and the Canadian cervical spines rule (CCR). Objectives : To evaluate imaging features of cervical spine fracture and to assess the anappropriateness of performing cervical spine CT according to NEXUS criteria and CCR at the emergency room of King Chulalongkorn Memorial Hospital (KCMH). Design : Retrospective study. Setting : King Chulalongkorn Memorial Hospital. Material and Methods : Our study recruited cervical spine CT images performed at the ER from November 2012 to October 2013 in adult patients suspected of acute cervical spine injury. Patients aged <18 years, non-acute trauma settings (≥ 72 hours), non-traumatic conditions, penetrating cervical injuries and refer red cases from other hospitals were excluded from this study. Results : Of the 150 cervical spine CT studies analyzed, 15 (10%) were positive for cervical fracture as followings; Clay shoveler fracture, burst fracture, transverse process fracture, Hangman’s fracture, dens/odontoid process fracture, hyperextension fracture dislocation and inferior endplate fracture. 137 (91.3%) patients with documented clinical indication for ordering cervical spine CT underwent cervical spine CT properly based on NEXUS criteria or CCR. The remaining 13 (8.7%) patients had no documentation about clinical indication but subsequent imaging showed no cervical spine fracture. Additionally, 51% (76/150) of the patients performed both cervical spine CT and cervical spine radiographs, in which being considered as “inappropriate”. Conclusions : Strict application of the ACR appropriateness criteria into practical use could reduce some CT over utilization and dramatically decrease the rate of unnecessary radiographs to clear the cervical spine.